Between sport and war: exploration of military terminology in the Moroccan and French sports press - El Mehdi Zerrad; Hassan BOUJGHAGH (International Journal of Scientific Research and Innovative Studies, 2025)
This study analyzes the use of military terms in sports journalism in France and Morocco, examining their impact on sports storytelling. Focusing on articles from 2021 to the present, it aims to decipher the cultural and social implications of these terms in football. The use of words like "battle," "offensive,"... shows how sports are sometimes perceived thru the prism of war, thereby questioning the motivations and perceptions of readers. Keywords: sports press, war metaphors, sports discourse, reception, ethos Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/455